The Influence of E-WOM and Celebrity Endorser on Instagram on Ortuseight Shoes Purchase Decisions - Anindita Lintangdesi Afriani; Dwi Indah Kinanti (Universitas Mataram, 2021)
The development of technology and information is increasingly advanced and rapid, making it easy for people to access the internet looking for various kinds of information. One source of information that is often accessed is social media, especially social media Instagram. The rise of the user's social media especially instagram provides opportunities that can be exploited for employers to do digital marketing, as did Ortuseight. Ortuseight is a local brand that was founded in 2018, with a focus on selling futsal and football shoes. Ortuseight promotes its products through e-wom which utilizes Instagram media and uses celebrity endorsers to give trust to consumers. The purpose of this study is analyze the influence of e-wom and celebrity endorsers on purchasing decisions shoes Ortuseight. This research method uses a quantitative approach, with multiple linear regression analysis techniques. Data collection for distributing questionnaires via google form to 50 people who have purchased Ortuseight shoes. The results of this study include: 1) e-wom partially has a significant effect on purchasing decisions; 2) celebrity endorsers partially do not affect purchasing decisions; 3) electronic word of mouth and celebrity endorser simultaneously have a positive and significant effect on purchasing decisions. This research concludes that simultaneously the e-wom and celebrity endorser variables have a positive and significant effect on purchasing decisions. However, a partially e-wom variable has a positive and significant influence on purchasing decisions. Keywords: e-wom, celebrity endorser, purchase decision, ortuseight.